L'université et les universitaires dans les mutations politiques et éducatives au Cameroun - Luc Ngwé; Hilaire De Prince Pokam; Albert Mandjack; Ernest Folefack (Les éditions de la Maison des sciences de l'Homme, 2006)
The Cameroonian university and its agents participated actively in the political process of the 90s in a country caught up in the double dynamic of the global restructuring of the role of the state and more specifically of the redefinition of education both at the international and locale levels in a changing socio-economic environment. In fact, political changes within or affecting the university transformed it into a stake and a political arena for professional politicians but also between communities participating in the management of Cameroon. Academics got involved in the political process as key actors playing various important roles. Students emerged as majors political actors in their role in the amplification of the political agitation and the mobilisation of less politicised social categories. The core of the academics involved in the political process were more inclined to participate in the formalisation and management of the democratic political order, this in pursuance of their long term strategy to be constantly party to the structuring, the definition and the management of the post-colonial state. This dynamic also brought about specific impetus to the reform operated in 1993 and the post-reform trajectories of Higher Education in Cameroon.